Combined EXAFS and DFT Structure Calculations Provide Structural Insights into the 1:1 Multi‐Histidine Complexes of CuII, CuI, and ZnII with the Tandem Octarepeats of the Mammalian Prion Protein. Issue 31 (7th July 2014) - Pushie, M. Jake; Nienaber, Kurt H.; McDonald, Alex; Millhauser, Glenn L.; George, Graham N.
Abstract The metal‐coordinating properties of the prion protein (PrP) have been the subject of intense focus and debate since the first reports of its interaction with copper just before the turn of the century. The picture of metal coordination to PrP has been improved and refined over the past decade, but structural details of the various metal coordination modes have not been fully elucidated in some cases. In the present study, we have employed X‐ray absorption near‐edge spectroscopy as well as extended X‐ray absorption fine structure (EXAFS) spectroscopy to structurally characterize the dominant 1:1 coordination modes for CuII, CuI, and ZnII with an N‐terminal fragment of PrP. The PrP fragment corresponds to four tandem repeats representative of the mammalian octarepeat domain, designated as OR4, which is also the most studied PrP fragment for metal interactions, making our findings applicable to a large body of previous work. Density functional theory (DFT) calculations have provided additional structural and thermodynamic data, and candidate structures have been used to inform EXAFS data analysis. The optimized geometries from DFT calculations have been used to identify potential coordination complexes for multi‐histidine coordination of CuII, CuI, and ZnII in an aqueous medium, modelled using 4‐methylimidazole to represent the histidine side chain. Through a combination of in silico coordination chemistry as well as rigorous EXAFS curve‐fitting, using full multiple scattering on candidate structures derived from DFT calculations, we have characterized the predominant coordination modes for the 1:1 complexes of CuII, CuI, and ZnII with the OR4 peptide at pH 7.4 at atomic resolution, which are best represented as square‐planar [CuII(His)4]2+, digonal [CuI(His)2]+, and tetrahedral [ZnII(His)3(OH2)]2+, respectively.